Students’ Perceptions of Context-Based Learning and Its Role in Developing Reading Skill - Asrul, Nurmahyuni; Meisuri, Meisuri (EXCELLENCE: Journal of English and English Education, 2024)
This study investigates students' perceptions of Context-Based Learning (CBL) and its effectiveness in enhancing reading skills, particularly in the context of digital and multicultural learning environments. A qualitative research design was employed, utilizing semi-structured interviews and open-ended questionnaires with 30 ninth-grade students at SMP Plus Shafiyyatul Amaliyyah. Thematic analysis was conducted to explore the students' experiences and perceptions regarding CBL. The findings revealed that students generally hold positive views toward CBL, with 85% reporting increased engagement when reading materials were connected to real-life contexts. Furthermore, 70% noted an improvement in their understanding of complex texts. However, challenges emerged in digital reading environments, as 60% of participants expressed difficulties in navigating digital platforms, which impacted their comprehension. Additionally, the integration of culturally relevant contexts significantly motivated students and enhanced their understanding of reading materials. This research fills a critical gap in understanding students' perspectives on CBL in relation to reading skills development. It highlights the importance of adapting CBL strategies for digital contexts and diverse classrooms to improve educational outcomes. The study calls for enhanced teacher training to effectively implement CBL in these settings. Keyword: Students’ Perception, Context-Based Learning, reading skill.